Acceleration of investment through the stabilization of money - Sriyono Sriyono (Universitas Hayam Wuruk Perbanas, 2014)
Indonesia downfall as represented in the economic crisis is due to the inability of the government to restore the pre-crisis level of investment in 1997. This could happen although the government has enforced Law No. 1 of 1967 Jo No 11 of 1970 on Foreign Direct Investment (FDI) and Law No. 6 Years 1968 Jo No 12 Year 1978 on Domestic Investment (DCI). This study attempts to reveal whether the investment is quite effective in accelerating investment through the stabilization of money. This is very important because the stabilization of money can raise investments, which finally affect greatly the condition of the state economy. The data were collected from 1970 to 2012. Econometric model is employed for testing the hypotheses because it can handle the mutual dependence (interdependence). Besides that, econometric model is an invaluable tool for understanding the way the economic system works and so to test and evaluate policy alternatives. Hypothesis is tested using multiple regressions with Two Stages Least Square method. The result shows that the stabilization of money could accelerate the investment by looking at the intermediate indicators on the exchange rate. However, it cannot be seen through the indicators of inflation.